Behavioral Factors of Dentists in Completing Electronic Medical Records: Scoping Review - Shafira Raudya Aidina; Chriswardani Suryawati; Farid Agushybana (International Journal Labs, 2023)
Ensuring comprehensive medical records is a crucial aspect of delivering effective healthcare in hospitals, with a particular focus on dental services. This research delves into the dynamics of the relationship between a dentist's behavior and the completeness of odontogram filling. The study focuses on a comprehensive analysis of performance expectations, effort expectations, social influence, and facilitating conditions. Through this examination, the goal is to positively influence dentist behavior, leading to improvements in the quality of odontography documentation. The findings aim to contribute valuable insights for enhancing dental practices. Adopting a qualitative research methodology with a scoping review approach, the investigation identifies various categories of dentist behavior in filling out electronic medical records. These categories are delineated based on the multifaceted aspects of performance expectations, effort expectations, social influence, and facilitating conditions. To augment the completeness of odontography filling, the research underscores the importance of considering the factors identified within these aspects. By addressing the nuanced interplay between these elements, interventions can be strategically designed to positively impact dentist behavior and, consequently, elevate the standard of odontography documentation. This research contributes valuable insights to the ongoing efforts aimed at refining the implementation of health services and ensuring meticulous medical record-keeping, particularly in the dental domain.